2013
DOI: 10.3109/0886022x.2013.832312
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glycemic control on microalbuminuria development among type 2 diabetes with high-normal albuminuria

Abstract: This study was aimed at revealing the factors and the interrelationships between factors on microalbuminuria development among type 2 diabetes (T2D) patients. Between 2004 and 2011, 461 T2D patients with a baseline urine albumin-to-creatinine ratio (UACR) of 530 mg/g, and an estimated glomerular filtration rate (eGFR) of 460 mL/min were evaluated retrospectively. Sixty-eight (14.8%) subjects had developed microalbuminuria in a mean follow-up of 6.82 years. Statistical analysis had revealed that the higher base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 26 publications
1
14
1
Order By: Relevance
“…The FSG in diabetic patients mean value was (12.20±4.64 m mol/L) and HbA1C mean was (8.24±1.84 %) which is significantly higher than the control group (mean FSG 5.12±0.63 m mol/L, HbA1C mean 4.62±0.88%), as summarized in (figure-1). There was no positive correlation between (FSG, HbA1c) and microalbuminuria, in contrast to a study by Chen et al (31) . Considering renal function assessment; the mean values of serum creatinine and estimated GFR were within normal range for both groups (Group A diabetics with positive microalbuminuria and Group B diabetics with negative microalbuminuria as shown in (figure-2) and ( figure-3).…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…The FSG in diabetic patients mean value was (12.20±4.64 m mol/L) and HbA1C mean was (8.24±1.84 %) which is significantly higher than the control group (mean FSG 5.12±0.63 m mol/L, HbA1C mean 4.62±0.88%), as summarized in (figure-1). There was no positive correlation between (FSG, HbA1c) and microalbuminuria, in contrast to a study by Chen et al (31) . Considering renal function assessment; the mean values of serum creatinine and estimated GFR were within normal range for both groups (Group A diabetics with positive microalbuminuria and Group B diabetics with negative microalbuminuria as shown in (figure-2) and ( figure-3).…”
Section: Discussioncontrasting
confidence: 98%
“…The level of glycemic control seems to be the strongest factor influencing transition from normoalbuminuria to microalbuminuria (31) . Glycemic control plays as vital role in diabetic microvascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…54 A study in Taiwan found that HbA1c is an indicator for microalbuminuria development among T2DM patients. 55 Among T2DM studies, glucose variability showed a positive association with the progression of DR. 54 A ten-year survey follow-up of diabetes patients in Taiwan showed that visit-to-visit glucose variations in both FPG-CV and HbA1c-CV independently predicted ESRD in patients with T2DM duration >30 years. 56 Some data show that glucose variability, namely, fasting plasma glucose variability, and retinopathy in T2DM patients have a possible connection.…”
Section: Dovepressmentioning
confidence: 99%
“…15 Chen et al explained the role of microalbuminria with glycemic control, with his results proving the relationship of high -normal albuminuria and glycemic control on microalbuminuria development among patients with diabetes mellitus type II. 16 Khalid et al showed in his study and proved the positive correlation between increased frequency of microalbuminuria and glycemic control. 17 Memon et al showed that by improving the glycemic control of diabetic patients, maintenance of the blood pressure can be ensured; and early diagnosis of the disease may decrease the risk of development and progression of microalbuminuria and finally end stage damage of kidney and mortality.…”
Section: Number Of Participants (%) Hba1c (%) P-valuementioning
confidence: 89%